Association Between Spasticity and Functional Impairments During the First Year After Stroke in Korea: The KOSCO Study. (August 2018) - Shin, Yong-Il; Kim, Soo-Yeon; Lee, Hae In; Kim, Deog Young; Lee, Jongmin; Sohn, Min Kyun; Lee, Sam-Gyu; Oh, Gyung-Jae; Lee, Yang-Soo; Joo, Min Cheol; Han, Eun Young; Han, Junhee; et al.
Abstract : Objective: The aim of the study was to investigate the correlation between spasticity severity and functional outcomes during the first year after stroke. Design: The Korean Stroke Cohort for Functioning and Rehabilitation is a large, multicenter, prospective cohort study of all patients with acute first-ever stroke admitted to participating hospitals in nine Korean areas. To investigate the correlation between spasticity severity and functional status measured by using the Institutes of Health Stroke Scale (NIHSS), Modified Barthel Index (MBI), Functional Independence Measurement (FIM), Fugl-Meyer Assessment (FMA), Functional Ambulatory Category (FAC), modified Rankin scale (mRS), and American Speech-Language Hearing Association National Outcome Measurement System Swallowing Scale (ASHA-NOMS), data were analyzed at 3, 6, and 12 mos after the occurrence of stroke. Results: A total of 7359 stroke patients, 3056 were finally included. Prevalence rates of spasticity in patients after stroke were 6.8% at 3 mos, 6.9% at 6 mos, and 7.6% at 12 mos. The scores of mRS and NIHSS were higher and those of K-MBI, FIM, FMA, and ASHA-NOMS were lower in more severe spastic patients, indicating poorer functional outcomes ( P < 0.05). Conclusions: This study demonstrated the coexistence of spasticity and poor functional outcome during the first year after first-ever stroke patients.